Pengembangan Media Pembelajaran Fisika Dengan Macromedia Flash Untuk Melatihkan Penerapan Konsep Siswa SMP - Andy Azhari; Mastuang Mastuang; Abdul Salam M. (Universitas Lambung Mangkurat, 2017)
This study is base on the low of media’s aplicability. But actually in the case is medias’ aplicability can help teacher to drill the students’ aplication concept. The purpose of this study is to produce physich learning’s media that suitable to use in drilling students’ aplication concept. The specific purfose of this study are (1) to describe the validity of physich learning’s media, (2) to discribe the practically of physich learning’s media based on lesson plan implementation during physics learning process, (3) to describe effectiveness of physich learning’s media based on students’ result test. This research and development used ASSURE (Analyze learner, state objectives, slect modify or design materials, utilize materials,require learner response and evaluate) design. The product result from this study is physich learning’s media with macromedia flash about optics. The study shows that: (1) The validity of learning media is categorized as good validity with a little correction, (2) the practically of learning media based on lesson plan implementation during physics learning process is categorized as practical, and (3) efectiveness of learning media based on students’ result test is categorized as effective. The conclusion of this research and development is physich learning’s media with macromedia flash is suitable to use in drilling the students’ aplication concept.